DISCOVERING THE BEGINNING OF TEACHING IN MATHEMATICS IN THE MULTI-SESSION CLASS - Muniz, Bruna Mendes [UNESP]; Ciriaco, Klinger (Univ Metodista Piracicaba-unimep, 2019)
We describe the results of a study that aimed to understand the organization of pedagogical work with mathematical contents in a multi-series class, located in the interior of the state of Mato Grosso do Sul. The methodological approach is inscribed in the field of qualitative research in descriptive- analytical. To this end, we used data from observing the practice of a beginning teacher, as well, as information taken from her class diary and the semistructured interview we developed. The theoretical framework adopted highlights issues related to the work with the Field Education, space of the teaching staff, multi-series classes and problems experienced at the beginning of the career. The collected data pointed out that communication in Mathematics classes has been presented as a possible way for both students and teachers to learn. In addition, the feelings of survival and discovery presented with great emphasis in the first year of professional experience, which corroborates the specialized literature on the subject.
Keywords: BEGINNING OF TEACHING; MULTISSERIES CLASS; MATHEMATICS TEACHING; TEACHING PRACTICE